Kajian Potensi Pariwisata Pantai di Wilayah Selatan Kabupaten Tasikmalaya - Winoto, Yunus; Damayani, Ninis Agustini; Husodo, Teguh; Siti Khadijah, Ute Lies (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2022)
This study aims to determine the potential of coastal tourism areas in the southern region of Tasikmalaya Regency. The research location was conducted at Sindangkerta Beach, Pamayang Beach, Cipatujah Beach, Bubujung Beach, Karangtowulan Beach, Cimanuk Beach, and Kalaparea Beach. The method used in this study uses a qualitative method by looking at the potential that exists in the southern region of Tasikmalaya Regency. Aspects used to analyze coastal tourism areas include attractiveness, accessibility, and facilities. The results showed that based on the analysis of three aspects, namely aspects of attractiveness, accessibility, and facilities, three coastal areas have the potential to be developed, namely Sessionkerta beach, Karangtowulan beach, and Pamayang beach. Meanwhile, other beaches such as Cipatujah beach, Bubujung beach, Cimanuk beach, and Bubujung Kalaparea beach are looking to have the potential to be developed by making improvements to several things such as aspects of facilities, both tourism facilities and public facilities. The management of coastal tourist destinations and the community in Tasikmalaya Regency pays attention to environmental preservation, and aspects of cultural preservation must be the principle of all parties involved in the development of the tourist area. Keywords: Attractiveness, Accessibility, Facilities